Study of Drell – Yan processes with the compact muon solenoid experiment at Large Hadron Collider - Gorbunov, Ilya N.; Lanyov, Alexander V.; Shalaev, Vladislav V.; Shmatov, Sergey V. (Journal of the Belarusian State University. Physics, 2019)
The results of measurements of the differential and double-differential cross sections (dσ/dM and d2σ/dMdy) of Drell – Yan processes in proton-proton collisions at 7 and 8 TeV in c. m. s. are presented. The double-differential cross section d2σ/dMdy has been studied in the range of the Bjorken scaling variable values 0.0003 < x± < 1.0 and the evolution scale 600 < Q2 < 750000 (GeV2/c2), and the differential cross section dσ/dM has been explored in a wider range 300 < Q2 < 3000000 (GeV2/c2). The measurements were performed in a combined channel with a pair of electrons and muons and are based on the experimental data of the Compact Muon Solenoid (CMS), collected during the first Large Hadron Collider (LHC) Run in 2011 and 2012. The statistic is corresponding to integrated luminosity of 5.1 fb–1 at 7 TeV and 20.6 fb–1 at 8 TeV. The measurements of the lepton forward-backward asymmetry AFB and the angular coefficients Ai are also discussed. These results agree within the uncertainty with the predictions of the standard model in the leading and next-to-leading orders.
Keywords: Large Hadron Collider; CMS experiment; Drell – Yan process; differential cross section; angular coefficients; forward-backward asymmetry